Development of rapidly constructible classrooms for disaster-stricken areas - Erni, Karlo Jon E.; Ong, Jonrick Aiken G.
The Philippines is geographically positioned along the Pacific Ring of Fire thus the country is frequented by typhoons, earthquakes and other natural disasters. Natural disasters may affect the community's livelihood and could also cause damage to the infrastructure in a community. Filipino students' education is affected as well; when classes are postponed for long periods of time due to unavailability of their classrooms that are either damaged and deemed unusable or used as evacuation areas.The Disaster Management Cycle (Dhameja, 2005) has five stages namely disaster preparedness and mitigation, disaster response, disaster relief, disaster rehabilitation and reconstruction and disaster recovery. This study focuses on the rehabilitation and reconstruction phase of the post disaster management cycle. It aims to develop a classroom design system that can be used during the restoration phase of damaged school facilities. The study developed a design scheme for rapidly constructible transitional classrooms, which complies with international and Philippines standards and guidelines for transitional classrooms.